Impact of an In-Field Teaching Degree on the Quality of Teaching as Measured by Student Performance - Mayfield, Elgin F.Jr. (Valdosta State University, 2011)
Recently, in both federal and state governments, legislation has been presented that would link teacher compensation to student performance on standardized tests. This change in compensation would abandon the traditional method of compensating teachers based on experience and level of degree earned. This study examines the relationship between student performance on the Criterion Referenced Competency Test and teachers earning Advanced In- Field education degrees. Many similar studies have been conducted on this topic, however the vast majority of those studies used either solely comparative analysis or utilized a value added model. Additionally, many of these studies do not differentiate the field of the advanced degree. This study uses a pre-test, post-test design to measure growth of teachers who have recently earned an Advanced In-Field degree and compares that growth to a control group of similar peers who have not recently earned an advanced degree. A statistically significant difference was discovered in both the control and the Advanced In- Field Degree groups between the pre-test and post-test. However, the difference in the Advanced In-Field Degree group was more highly significant than the control, indicating that the Advanced In-Field Degree group did outpace the control.
Keywords: Teacher Compensation; Competency Test; Field Degree; Mayfield; Educational change--United States